Resistance of Phytophthora infestans in three Solanum nigrum F3 families - Śliwka, Jadwiga; Tomczyńska, Iga; Chmielarz, Marcin; Stefańczyk, Emil; Lebecka, Renata; Zimnoch-Guzowska, Ewa (Plant Breeding and Seed Science, 2012)
Solanum nigrum is a self-pollinating, hexaploid weed and one of a few Solanaceae species native to Europe. It used to be described as a non-host for Phytophthora infestans. However, now it is known that, like its distant relatives: potato (Solanum tuberosum L.) and tomato (Solanum lycopersicum L.), S. nigrum can suffer from potato late blight caused by this pathogen. Both susceptible and resistant S. nigrum genotypes have been previously identified and inheritance of resistance originating from one accession has been described based on population of F2 plants and 15 F3 lines. The goal of this study was to evaluate resistance of three families of F3 lines, originating from crosses between a susceptible and three different resistant S. nigrum accessions followed by two self-pollinations. Parental acces- sions were tested for the spectrum of late blight resistance against 48 P. infestans isolates. The three families consisted of 106, 96 and 115 F3 lines, respectively, and from each line 20 plants were tested for resistance to P. infestans. Laboratory detached leaf assays were performed in two dates and two replications of three leaves each. Segregation of the trait within the line allowed us to distinguish hetero- and homozygous lines. In one F3 family, the ratio of resistant homozygotes: heterozygotes: susceptible homozygotes was 1:2:1, indicating that a single gene is most likely underlying the late blight resistance in this case. In the other two, observed segregations of the trait significantly deviated from this model suggesting more complex inheritance patterns.